Performance of Grouted Splice Sleeve as A Connection for Wall Panels - Ling, Jen Hua; Abd. Rahman, Ahmad Baharuddin; Ibrahim, Izni Syahrizal (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2024)
A grouted sleeve is a mechanical coupler used to join steel bars. It can be used to join precast concrete walls. Most grouted sleeves are pricey proprietary products. This study investigated the behaviour of a grouted sleeve made of steel pipe sections. The grouted sleeve was used as a wall panel connection. The specimens were subjected to three types of loads: tensile, shear, and flexural. The performance of the specimens was evaluated based on the load-displacement responses. For satisfactory bond strength, a bar embedded length of 11 times the bar diameter was required. The grouted sleeve performed well in tension but poorly in shear load. The service shear load was just one-third of the total load capacity. Thus, the grouted sleeve was not recommended for resisting shear load without shear keys to strengthen the joint.